ANALISIS PENGARUH PENJUALAN ADAPTIF DAN ORIENTASI SMART-WORKING TERHADAP KINERJA BISNIS IBO - wisnu yusditara (Fakultas Ekonomi dan Bisnis, Universitas HKBP Nommensen, 2020)
This study aims to look at the effect of adaptive sales and smart-working orientation on IBO Oriflame business performance. This study uses multiple regression analysis with a sample size of 96 respondents. the results show that IBOs able to adapt well in making sales will improve the business performance of the IBO. IBO who work smartly in building their business cannot improve their business performance. The inability of smart work in building business networks caused by most respondents who are still new to the Oriflame MLM business.